Kebijakan Makan Bergizi Gratis di Indonesia di bawah Presiden Prabowo: Analisis Kebijakan, Fiskal, dan Politik Berdasarkan Bukti Internasional - Markus Hadinata (Jurnal Bina Praja, 2026)
The Free Nutritious Meal (Makan Bergizi Gratis [MBG]) program is a strategic government policy introduced under President Prabowo Subianto of Indonesia, aimed at improving children's nutritional status, reducing stunting, and strengthening human resource quality. Although the benefits of school feeding programs are well established globally, comprehensive studies on the effectiveness of the MBG program within Indonesia's regulatory and institutional capacity context remain limited. This article analyzes the MBG program using an evidence-based public policy approach and a political economy lens, drawing on a review of Scopus-indexed international journal articles, academic books, and the national regulatory framework. The analysis indicates that school feeding programs have positive effects on children's nutritional status, school attendance, and learning outcomes; however, their effectiveness is strongly influenced by governance quality, food safety, cross-sectoral coordination, and fiscal sustainability. In light of these findings, this article argues that the MBG program holds considerable potential as a transformational policy. Nonetheless, without sound fiscal design, strengthened institutional capacity, and robust public accountability mechanisms, the policy risks becoming a costly and unsustainable populist intervention.